European asylum law and the rights of the child - Smyth, Ciara (Routledge research in asylum, migration and refugee law, 2014)
"In the last decade the European Union has increasing engaged with children's rights. In 2007 European Court of Justice (as it was then) referred for the first time to the Convention on the Rights of the Child as an international instrument to which it has regard in the interpretation of general principles of EC law. With the entry into force of the Lisbon Treaty in December 2009 a new Article 3(3) of the Treaty on European Union commits the Union to promoting the 'protection of the rights of the child.' This book addresses the question of whether the Common European Asylum System (CEAS) complies with the rights of the child. It contrasts the normative standards of international child rights law with the standards of treatment of child asylum seekers and refugees in the CEAS. More particularly, the book identifies the attributes of the rights of the child that are most relevant to the asylum context and systematically examines whether and to what extent those attributes are reflected in the existing and proposed recast CEAS legislation. The book goes on to assess whether the CEAS instruments direct Member States, without more, to act in such a way as complies with the rights of the child in order to offer a comprehensive examination of the place of the child within European asylum law and policy"--